Histomorphometric study of thyroid gland of Bangladeshi people - Sultana, SZ; Khan, MK; Sultana, S; Rahman, MH; Khalil, M; Khalil, M (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jan;16(1):36-42.The abstract of this article is available on the PubMed website